PENERAPAN STRATEGI PEMASARAN UNTUK MENINGKATKAN DAYA SAING UMKM TOKO KELONTONG IBU DUSMI DI DESA KEJENE - Benopitasari; Hendri Hermawan Adinugraha; Ade Gunawaan (Jurnal Manajemen dan Pemasaran, 2025)
Traditional grocery stores in Kejene Village are facing significant challenges in sustaining their businesses amidst tight competition with modern minimarkets that offer more practical services and a wider variety of products. The main problem lies in the lack of effective marketing strategies, making it difficult for traditional stores to compete and attract customers. To address this issue, this study aims to identify suitable marketing strategies to enhance the competitiveness of traditional grocery stores. A qualitative approach was used, involving direct interviews with store owners, observations, and literature studies. Preliminary findings indicate that applicable marketing strategies include improving customer service, organizing products more attractively, adjusting prices, and promoting through social media or word of mouth. In addition, a personal approach such as building good relationships with customers has proven to increase customer loyalty. With the right and consistent strategies, traditional grocery stores have the potential to survive and thrive despite competitive pressure. This research is expected to serve as a reference for other small business owners striving to remain independent and sustainable. Keywords: Traditional Grocery Store; Marketing Strategy; Business Competition